The law on the use of force : a feminist analysis - Heathcote, Gina. (New York : Routledge, 2011)
'The book presents the international laws on the use of force whilst demonstrating the unique insight a feminist analysis offers this central area of international law. The book highlights key conceptual barriers to the enhanced application of the law of the use of force, and develops international feminist method through rigorous engagement with the key writers in the fieldThe book looks at the key aspects of the UN Charter relevant to the use of force Article 2(4), Article 51 and Chapter VII powers as well as engaging with contemporary debates on the possibility of justified force to meet self-determination or humanitarian goals. The text also discusses the arguments in favour of the use of pre-emptive force and reflects on the role feminist legal theories can play in exposing the inconsistencies of contemporary arguments for justified force under the banner of the war on terror. Throughout the text state practice and institutional documentation are analysed, alongside key instances of the use of force. The book makes a genuine, urgently needed contribution to a central area of international law, demonstrating the capacity of feminist legal theories to enlarge our understanding of key international legal dilemmas'--
'This book provides a comprehensive feminist analysis of the relationship between international law on the use of force (law of war) and legal constructions of gender from the perspective of feminist approaches to international law. Topics covered within the book include an analysis of the collective security regime under the United Nations system and the developing powers of the Security Council, as well as a critical review of the five Security Council resolutions on women, peace and security. Throughout the text, state practise and institutional documentation are analysed alongside key instances of the use of force. Additionally, the author provides a review and analysis of the US 2010 National Security Strategy and the policies of the Obama administration'--
Feminist legal approaches and international law on the use of force -- Collective security -- Justifying force : self-defence -- Justifying force : self-determination -- Justifying force : humanitarian intervention.
Keywords: War (International law); Intervention (International law); Feminist jurisprudence